2019
DOI: 10.3390/pr7050303
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Macroalgal Density and Salinity for Nutrient Removal by Caulerpa lentillifera from Aquaculture Effluent

Abstract: Determining the optimum levels of macroalgal density and salinity for removing aquaculture effluent has gained increasing research interest in recent years because of the growing concerns over environmental sustainability. Here, we determined the effects of macroalgal density and salinity on the uptake of NO2−, NO3−, NH3, and PO43− by Caulerpa lentillifera from the effluent of Poecilia latipinna using spectrophotometry. Laboratory experiments were conducted to measure nutrient uptake at five different macroalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The C:N ratio also helps determine whether the macroalgae are faced with a condition of deficiency in N. When it exceeds 15, it means that N is limited. In our study, both the initial and final C:N ratios indicate that there was no N limitation for seaweed growth [35,46].…”
Section: Macroalgae Growthmentioning
confidence: 47%
See 3 more Smart Citations
“…The C:N ratio also helps determine whether the macroalgae are faced with a condition of deficiency in N. When it exceeds 15, it means that N is limited. In our study, both the initial and final C:N ratios indicate that there was no N limitation for seaweed growth [35,46].…”
Section: Macroalgae Growthmentioning
confidence: 47%
“…These conditions were applied to the outdoor experiment in the current study to run the integrated circulation system. In addition, water motion or bubbling is crucial for the nutrient uptake and macroalgal growth [35], and aeration showed a positive effect on nutrient uptake by C. lentillifera in laboratory experiments [34]. Therefore, macroalgal culture units were aerated using fish culture units, and seaweed units were aerated using air stones.…”
Section: Fish-seaweed Integrated Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies showed that the seaweed might even be used in medicine as an anti-diabetic agent [7] and dye industries [8,9]. Besides those properties, C. lentillifera has shown the potential ability to remove nutrients from aquaculture effluent [10][11][12][13] and heavy metals from wastewater [9,14]. However, it has been documented that their culture in ponds might become a problem because they absorb heavy metals [3] and for this reason, it might be interesting to culture them in a controlled system.…”
Section: Introductionmentioning
confidence: 99%